Identification of semiochemicals evoking behavioral response in the Selangor strain aedes aegypti (L.) - Nurulhusna, Ab. Hamid (2011)
Semiochemicals are chemical substances or mixtures of chemicals substances which act as messengers between or within the insect species, regulating the behavior of other individuals. Identification of specific semiochemicals and its behavior regulating property can provide leads for designing target specific, nontoxic, environmentally less persistent insecticide which is difficult for insects to develop resistance against. This study was conducted to identify semiochemicals of the Selangor strain Aedes aegypti (L.), an important vector for dengue in Malaysia, and to observe their behavioral response toward n-hexane extract of mosquitoes of various age groups. Behavioral bioassay was conducted in a customized Y-tube olfactometer. Male mosquitoes 3 days to 6 days post-emergence were found to be attracted to 6 days to 15 days post-emergence male n-hexane extracts and 1 day to 9 days post-emergence n-hexane extracts of females. Meanwhile, female mosquitoes 3 days to 6 days post-emergence were attracted to 1 day to 3 days post-emergence male n-hexane extracts and 6 days to 15 days n-hexane extracts of females. n-Hexane extracts of Aedes aegypti of various age groups and separate body parts of unmated and mated insects were analyzed via GC-FID and GCMS. Chromatographic analysis revealed that n-alkanes contributed toward 40 % of the total chemical composition in the n-hexane extracts of mosquitoes of various ages. n-Heptacosane was detected in greatest abundance in both male and female n-hexane extracts, followed by n-tetratriacontane and the C30 mixture. 3β-Cholest-5-en-3-ol (cholesterol), followed by n-heptacosane occurred in abundance in n-hexane extracts of the various male body parts. 3β-Cholest-5-en-3-ol (cholesterol) was the major compound detected in the n-hexane extract of female body parts. The percentage of a number of identified compounds, viz. n-pentacosane, n-heptacosane and 3β-cholest-5-en-3-ol, in the n-hexane body parts extract was found to have increased in mated groups of the mosquitoes. HS-SPME-GCMS on live Aedes aegypti detected n-heptadecane as the most abundant compound secreted by both males and females during the 16 hours incubation period. Chemical analysis of extracts and secretions of the Aedes aegypti throughout its life revealed mostly n-alkanes occupied as major compounds. Longer carbon chains (> C20) extracted from the insect cuticular were found to dominate the n-hexane extracts. On the contrary HS-SPME-GCMS analyses were dominated by shorter chain carbons (< C20) secreted from the Aedes aegypti glands.